Secnidazole for treatment of bacterial vaginosis: a systematic review - Mohamed A. Abd El Aziz; Foruzan Sharifipour; Parvin Abedi; Shayesteh Jahanfar; Helen Marie Judge (BMC, 2019)
Abstract Background Bacterial vaginosis (BV) is one of the common vaginal infections among childbearing women. The usual treatment for BV is metronidazole; hence 30% of women have recurrence within 60 to 90 days after treatment. There are some studies which assessed the effect of secnidazole on BV. The aim of this systematic review was to investigate the effectiveness of secnidazole for treatment of BV. Methods The Cochrane Library, MEDLINE (PubMed), Scopus, and Web of Science (all databases from inception till October 28, 2018) were searched. Primary outcomes were clinical cure rate and microbiologic cure rate and the secondary outcomes were adverse events. Data was extracted from eligible studies by two review authors individually and analyzed by RevMan 5.3. Results Our search found six trials involving 1528 participants. Treatment with 2 g secnidazole could significantly reduce the risk of BV in patients with three or less episodes of BV in the last year by OR: 7.54 (95% CI, 3.89-14.60, p < 0.00001) and in patients with four or more episodes of BV in the last year (OR: 4.74, 95% CI: 1.51-14.84, p = 0.0.008). Secnidazole (2 g) could significantly increase the microbiologic cure rate in women with 3 or less episodes of BV in the last year (OR: 7.63, 95% CI: 2.30-25.33, p = 0.0009) but not in the women with 4 or more episodes of BV in the last year (OR: 20.17, 95% CI: 1.06-382.45, p = 0.05). The clinical cure rate, microbiological effect and the therapeutic cure rate of 2 g secnidazole was significantly more than that of 1 g secnidazole. The results showed that the clinical cure rate of 2 g secnidazole was not different from the following medications: metronidazole (500 mg bid for 5 days), secnidazole plus vaginal metronidazole, 2 g single dose of oral metronidazole and 2 g secnidazole plus vaginal ornidazole. Conclusion This review showed that 2 g and 1 g secnidazole were better than placebo, however, 2 g secnidazole was more effective than 1 g. Secnidazole 2 g was not different from metronidazole (500 mg bid for 5 days), or from secnidazole plus vaginal metronidazole, or 2 g single dose of oral metronidazole or from 2 g secnidazole plus vaginal ornidazole.